Modulational instability of the electron cyclotron waves in an adiabatic wave - particle interaction - Hakimi Pajouh, H.; Abbasi, H. (Вопросы атомной науки и техники, 2002)
Modulational instability of a circularly polarized electromagnetic wave, propagation along an external constant magnetic filed in plasma is investigated. The method is based on the derivation of a nonlinear Schrodinger equation, which contains nonlinear terms associated with trapped electrons and also relativistic electron quiver velocity. Among different mechanisms of trapping the collision-less process is considered. Since we are interested in characteristic spatial scales larger than the Debye length, the condition of quasi-neutrality is assumed. The maximum growth rate is calculated and the result shows that the trapped particles prevent the spatial localization of the electron cyclotron waves.